A 3D-Printed High Power Nuclear Spin Polarizer - Nikolaou, Panayiotis (J Am Chem Soc, 2014)
[Image: see text] Three-dimensional printing with high-temperature plastic is used to enable spin exchange optical pumping (SEOP) and hyperpolarization of xenon-129 gas. The use of 3D printed structures increases the simplicity of integration of the following key components with a variable temperature SEOP probe: (i) in situ NMR circuit operating at 84 kHz (Larmor frequencies of (129)Xe and (1)H nuclear spins), (ii) <0.3 nm narrowed 200 W laser source, (iii) in situ high-resolution near-IR spectroscopy, (iv) thermoelectric temperature control, (v) retroreflection optics, and (vi) optomechanical alignment system. The rapid prototyping endowed by 3D printing dramatically reduces production time and expenses while allowing reproducibility and integration of “off-the-shelf” components and enables the concept of printing on demand. The utility of this SEOP setup is demonstrated here to obtain near-unity (129)Xe polarization values in a 0.5 L optical pumping cell, including ~74 ± 7% at 1000 Torr xenon partial pressure, a record value at such high Xe density. Values for the (129)Xe polarization exponential build-up rate [(3.63 ± 0.15) × 10(−2) min(−1)] and in-cell (129)Xe spin−lattice relaxation time (T(1) = 2.19 ± 0.06 h) for 1000 Torr Xe were in excellent agreement with the ratio of the gas-phase polarizations for (129)Xe and Rb (P(Rb) ~ 96%). Hyperpolarization-enhanced (129)Xe gas imaging was demonstrated with a spherical phantom following automated gas transfer from the polarizer. Taken together, these results support the development of a wide range of chemical, biochemical, material science, and biomedical applications.